Correlation between MDA Level and Chitotriosidase-1 Activity in Seminal Fluid of Iraqi Infertile Males - Ali S. Abdul Aziz; Hedef D. Elyaseen; Hussain K. Kadhem (مجلة كلية الطب, 2024)
Background: Male infertility is a multifactorial condition influenced by various physiological and biochemical factors. Seminal fluid composition plays a crucial role in sperm function and fertilization potential. Chitotriosidase is a chitinase enzyme released by activated macrophages and is highly conserved and controlled. The notable chitinase in humans plays a significant role in the body's immunological response and is linked to inflammation, infection, tissue damage, and remodeling processes. On the other hand, malondialdehyde is a marker of lipid peroxidation, reflecting oxidative stress levels.